PENGARUH PENGGUNAAN MEDIA FLIPBOOK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS III SDN 1 JAMBLANG - Rizki Kurnia, Andine; Nurhabibah, Prabawati; Wahyuningsih, Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low reading comprehension ability of third grade students at SDN 1 Jamblang in understanding reading materials and the lack of variety in the use of media in the learning process of reading skills. This study aims to determine the effect of using flipbook media on reading comprehension skills of third grade students of SDN 1 Jamblang. This type of research is quantitative research with Pre-Experimental Design, the form of design used is One-Group Pretest-Posttest Design. This research was conducted at SDN 1 Jamblang with a sample of 30 students. Sampling using saturated sampling technique. Data collection used, namely test techniques to measure the reading comprehension skills of third grade students. Data analysis technique to test the hypothesis using Paired Sample T-Test obtained Sig. (2-tiled) level of 0.000, where 0.000 < 0.05, it can be concluded that H0 is rejected and Ha is accepted. The result of this study is that there is a significant effect of using flipbook media on the reading comprehension ability of third grade students of SDN 1 Jamblang. In addition, based on the average pretest results of 70.00 and the average posttest results of 85.80.